2020
DOI: 10.1016/j.cjca.2020.02.081
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress: A Unifying Paradigm in Hypertension

Abstract: The etiology of hypertension involves complex interactions among genetic, environmental, and pathophysiologic factors that influence many regulatory systems. Hypertension is characteristically associated with vascular dysfunction, cardiovascular remodelling, renal dysfunction, and stimulation of the sympathetic nervous system. Emerging evidence indicates that the immune system is also important and that activated immune cells migrate and accumulate in tissues promoting inflammation, fibrosis, and target-organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
148
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(163 citation statements)
references
References 156 publications
(206 reference statements)
4
148
0
11
Order By: Relevance
“…Potential biological pathways may include oxidative stress leading to impaired vasodilation [34][35][36][37]. Oxidative stress is proposed to play a critical role in the pathogenesis of hypertension [38,39]. Moreover, intra-uterine exposure has been shown to reduce the number of nephrons at birth [40], which may be associated with over-activation of existing nephrons, pressure natriuresis, and blood pressure elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Potential biological pathways may include oxidative stress leading to impaired vasodilation [34][35][36][37]. Oxidative stress is proposed to play a critical role in the pathogenesis of hypertension [38,39]. Moreover, intra-uterine exposure has been shown to reduce the number of nephrons at birth [40], which may be associated with over-activation of existing nephrons, pressure natriuresis, and blood pressure elevation.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies which reported persistently increased ROS levels in HT, along with vast improvement upon antioxidative treatment [121][122][123][124][125][126][127]. HT is connected with vascular remodeling, increased vasoconstriction and arterial stiffness, activation of immune cells, renal dysfunction, and excitation of sympathetic nervous system.…”
Section: Hypertension and Oxidative Stressmentioning
confidence: 99%
“…HT is connected with vascular remodeling, increased vasoconstriction and arterial stiffness, activation of immune cells, renal dysfunction, and excitation of sympathetic nervous system. Above phenomena are inseparably connected with endothelial dysfunction, LPO, inflammation, fibrosis and more, thus favoring the notion that OxS constitutes a common molecular phenomenon in multifactorial pathogenesis of HT [122]. Cardiovascular cells generate ROS due to action of several major enzymes: NOX, XOR, ERO, and uncoupled NOS.…”
Section: Hypertension and Oxidative Stressmentioning
confidence: 99%
“…Potential biological pathway may include oxidative stress leading to impaired vasodilation [32][33][34][35]. Oxidative stress is proposed to play a critical role in the pathogenesis of hypertension [36,37]. Moreover, intra-uterine exposure has been shown to reduce the number of nephrons at birth [38], which may be associated with over-activation of existing nephrons, pressure natriuresis, and BP elevation.…”
Section: Discussionmentioning
confidence: 99%